FACTORS INFLUENCING STICKY COST BEHAVIOR - Manodamrongsat, Pornthip (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2024)
Sticky cost behavior arises from asymmetric decisions by management in estimating expenses or costs. It causes cost increases and decreases to be unequal, while activity volumes increase and decrease to be equal. From the study, it can be concluded that the factors that influence sticky cost behavior are: 1) Employee intensity is related to sticky cost behavior. 2) Debt intensity is negatively related to sticky cost behavior. 3) Corporate governance can help reduce sticky cost behavior. 4) Firms with fewer resources show signs of adjustment in their cost behavior. 5) Developing countries are able to adjust costs well when incomes are falling. 6) The level of sticky costs increases as GDP increases. Results from the study of factors that influence the sticky cost behavior, investors can consider and screen companies in which to invest in order to reduce risks and financial losses. Executives can use the results of the study to consider adaptation and problem-solving. The results obtained are useful for accounting instructors in teaching their students.